The Military and Teens: The Ultimate Teen Guide - Gay, Kathlyn (Rowman & Littlefield Publishers, 2008)
The Military and Teens covers the major issues young adults should consider before making a decision to join the armed forces. Although each branch of the military provides print and electronic materials on what it has to offer enlistees, very few YA books take a pro-and-con look at military service. Moreover, commercial military books mostly cover specific wars or give tips on surviving induction and training. From deciding to serve, to what it's like to face death, to being forced to kill, to discrimination in the military, and to life afterwards, this work presents the benefits and downsides of military service. Kathlyn Gay covers the many available choices of careers in the military and points out where to go for more information. Both primary and secondary sources have been used to provide information on young participants in the American Revolutionary War, War of 1812, Civil War, World Wars I & II, as well as the Korean, Vietnam, and Gulf wars. In the final pages of the book, the comprehensive list of available sources of information includes books, magazine articles, and websites for further research. Enhanced by young people sharing their personal experiences as enlistees and as members of military families, The Military and Teens is a useful resource for both teens and those who work with teens to advise them on career choices.